Monotonic and fatigue properties of kenaf/glass fiber-reinforced hybrid composites - Kashkol, Mohaiman Jaffar (2016)
The range of applications involving natural fiber composites in engineering design is still limited due to a lack of understanding of the long-term behavior of these materials, especially under cyclic fatigue loading. The primary aim of this research was to experimentally determine the monotonic properties and fatigue life behavior of woven kenaf fiber reinforced unsaturated polyester composites and the effects of hybridization of E-glass fabric on these properties through stages of hybridization and different states of stress. This work was divided into four stages to achieve the specified objectives. The first stage investigated the mechanical properties of a single layer of woven kenaf reinforced unsaturated polyester, fabricated by vacuum infusion and hand lay-up. The results showed an overall improvement in tensile and flexural strengths also their corresponding moduli for composites fabricated by the hand lay-up when compared with the ones fabricated by vacuum infusion. Therefore, hand lay-up method was adopted to fabricate the hybrid composites in the next stages. The second stage focused on comparing the effect of kenaf fiber alignment on the monotonic and fatigue properties of kenaf/glass hybrid composites laminate with glass shell and kenaf core. Three types of kenaf fibers were used, namely, non-woven random mat, unidirectional twisted yarn, and plain-woven kenaf with kenaf/glass weight ratio of 30/70% and a volume fraction of 35%. Tensile, compression, flexural, and fully reversed fatigue tests were conducted. Non-woven mat kenaf hybrid composite showed the poorest properties for all tests, while woven and unidirectional kenaf displayed much higher set of properties. Hybridization with kenaf fibers improved the fatigue degradation coefficient of the final composites to 6.6% and 6.8% for woven and unidirectional kenaf, respectively, compared with 8.4% for non-woven. The third stage was continued with a partial replacement of glass fiber by woven kenaf fabric reinforced unsaturated polyester. The replacement was achieved in three weight ratios of 70/30 (H1), 55/45 (H2) and 30/70 (H3) to fabricate hybrid composites. In addition, pure glass and kenaf composites were fabricated for comparison purposes. All composites had an approximate fiber volume fraction of 35-40%. Tensile, compression, and flexural tests were performed. Finally, the fourth stage, based on the ultimate static strength determined, uniaxial cyclic fatigue tests were conducted under three different stress ratios (R) of 0.1 (Tension-Tension), -1 (Tension-Compression), and 2.5 (Compression-Compression). Stress levels ranged from 30% to 70% of their ultimate static strength were used with R = 0.1 and -1, and from 40% to 90% of ultimate static strength with R = 2.5. Wohler S-N curves were generated for each stress ratio for all composites, which were used to construct a constant life diagrams for each composite. In conclusion, hybridization of glass fiber with kenaf fiber showed unique and improved influence on monotonic as well as fatigue properties.